Alternatives of surface treatments for adhesion of lithium disilicate ceramics - Alberto Carlos-Cruz Gonzalez; Edgar-Delgado Mejía (Editorial Ciencias Médicas, 2018)
Introduction: the clinical success of a restoration is strongly associated with the quality and durability of the ceramic-cement resin interface. In order to obtain an adequate union between these materials of different nature surface treatments are used and achieve mechanical retention or chemical interaction. Objectives: to check if any method promotes a true chemical bond between lithium disilicate ceramics and resin cement. As well as determineif there is any treatment that reports bonding values comparable to hydrofluoric acid and silane (gold standard). Methods: a systematic literature review was developed based on the PRISMA strategy, where the databases were searched: Science Direct, Pubmed (MEDLINE), EMBASE, Springer Journal, SciELO with MeSH and free terms from 2005 to November 2016 for articles in English and Spanish on surface treatments for lithium disilicate. Results: from 58 publications selected a sample of 21 articles. Two articles reported high risk of bias. Conclusions: hydrofluoric acid and silane continue to be the method with the highest and most reliable adhesion values in the literature. Universal adhesives are an alternative to promote chemical adhesion additional to the silane. Diamond burs, Nd: YAG and Er: YAG laser are not recommended as surface treatments.